Performance of bentonite and kenaf mixtures as grounding enhancement materials - Wan Ahmad, W. F. H.; Mohamad Roslan, M. H.; Jasni, J.; Ab-Kadir, M. Z. A. (IEEE, 2023)
The vital reason of having a grounding system in any power system installation is safety. There is a need to ensure that any fault current could be dispersed into soil at the shortest time possible during both normal and fault circumstances. There are many ways to be done in order to obtain the best grounding system with low earth resistance values. In one of the way is by adding NEM to the soil in the vicinity of a vertical ground conductor. This study employed four vertical ground conductors that were installed with NEM to investigate their performances, environmental and economic effects, and compared to a Reference grounding system with no NEM added in the vicinity of the ground conductor. The chosen NEM were Bentonite and Kenaf, as both materials are able to absorb and retain moisture in the surrounding soil. Four different mixtures of such NEMs were employed, i.e., 100% Bentonite, 100% Kenaf, Bentonite and Kenaf Mix A, and Bentonite and Kenaf Mix B. Note that these grounding systems were installed at a spacious site near to SGS, UPM where earth resistance of each grounding system was measured daily for 5 months, starting from 19$^{th}$ December 2016 until 18th May 2017. It is found that after 150 days, the performance of the grounding systems in descending order were 100% Bentonite, Bentonite and Kenaf Mix A, and Bentonite and Kenaf Mix B, Reference, and 100% Kenaf grounding systems, with 20.74%, 41.66%, 43.59%, 93.27% and 103.50% measured earth resistance value compared to the day-0 earth resistance value of the Reference grounding system, respectively. This clearly demonstrated that 100% Bentonite is much better NEM to be used in grounding system installations compared to 100% Kenaf. However, Mix A grounding system also showed a promising performance once in a while, while Mix B did not. Therefore, it could be compelling to further explore the behaviour of mixing Bentonite and Kenaf as grounding enhancement materials with other various ratios for future works. Note that Bentonite ratio was more in Mix A compared to Mix B.